GNSS Tools Used in Teaching Geography and Cartography: Methodological Aspects - Cedeño-Montoya, Bepsy (2018)
The article presents the main methodological aspects acquired during the two years of execution of the project "Application of the GPS tool in the teaching of Cartography". It describes the methodology used, detailing the processes and steps followed to meet the objectives, tasks and activities proposed in the formulation of the project. It describes the different technical phases, indicating the programs and tools used, as well as the main difficulties faced in each process. In addition, the main products are shown: the high precision point spatial data bank, the mosaic of georeferenced aerial photographs and the mosaic of orthorectified images, performing an analysis of the results obtained and presenting the main conclusions and recommendations derived from the methodological process developed.